Performance Evaluation of Reinforced Geopolymer Concrete as Earthquake Resistant Composite - N. B. Mahantesh (New Approaches in Engineering Research Vol. 15, 2021)
With the increasing challenges of ground vibrations due to seismic activity and an ever-increasing threat possibility of blast loadings on structures, it has become more than a mere necessity to incorporate robust design strengths into structure without affecting the serviceability life. The performance of structural elements is well appreciated, when their ability to absorb and dissipate energy by post elastic deformations subjected to several cycles of these loading are naturally imbedded at low cost. Ductility of flexural element is the only chief governing property for healthy performance of structural element. Although numerous factors contribute towards ductility of Reinforced Geopolymer Concrete (RGPC), low calcium-based fly ash and GGBS have chemical proportions which make RGPC develop significant ductility along with steel reinforcement, when they are mixed in an intelligent way satisfying structural and economic conditions. In the present research work influence of low calcium fly ash, GGBS, River sand, M-sand, Steel Grade, manufactured fibers and natural fibers on ductile behavior of RGPC are studied by load testing 51 under reinforced flexural elements. Similar tests done by other researchers on the flexural ductilites of Ordinary Portland Cement based flexural elements indicate Reinforced Geopolymer Concrete Structural Elements are highly comparable and appreciated.